Social, political and legal determinants of kidney health: Perspectives from lower- and middle-income countries with a focus on India - Anandh, Urmila; Meena, Priti; Karam, Sabine; Luyckx, Valerie (Frontiers in Nephrology, 2022)
Abstract The social determinants of health (SDoH) are the non-medical factors that influence kidney health outcomes directly or indirectly in a substantial manner and include conditions in which people are born, grow, work, live, and age. Many such challenges in lower- and middle- income countries have an unfavourable impact on kidney health. These conditions potentially influence economic policies and systems, development agendas, social norms, social policies, and political systems. In addition, many political and legal factors also determine and modify the ultimate outcome in patients with kidney disease. Converging lines of evidence have supported the impact of social variables such as socioeconomic resources, social inclusion, housing conditions, educational attainment, and financial status on kidney health. particularly affect vulnerable and disadvantaged groups and result in challenges in kidney care delivery. Furthermore, the climate is an important SDoH that plays a crucial role in the occurrence, prevalence, and progression of kidney diseases as highlighted by the presence of higher prevalence of chronic kidney disease in hot tropical countries. The rising incidence of water and vector-borne diseases causing acute kidney injury is another consequence of disruptive environmental and climate change which is detrimental to kidney health Political risk factors such as conflict also have a devastating influence on kidney health. The relationship between SDoH and kidney health outcomes requires more clarity. Gaps in the current knowledge need to be identified to inform the development of appropriate interventions to address upstream socio-economic risk factors for kidney disease .